Investigation of clinical utility of contrast-enhanced MRI in the diagnosis of ectopic pregnancy. Issue 7 (July 2020) - Nishio, N.; Kido, A.; Kurata, Y.; Minami, M.; Tokunaga, K.; Honda, M.; Mandai, M.; Togashi, K.
Abstract : AIM: To investigate whether contrast-enhanced (CE)-magnetic resonance imaging (MRI) improves identification of implantation site of ectopic pregnancy. MATERIALS AND METHODS: This retrospective study enrolled 63 patients in whom implantation sites had been confirmed at histopathology. Two expert radiologists for gynaecological imaging and two inexpert radiologists independently reviewed non-CE MRI and a combination of non-CE and CE-MRI (non-CE+CE-MRI), then determined implantation site with a confidence level. The following MRI features were also evaluated: extrauterine gestational sac (GS)-like structure (shape, signal intensities at T1-weighted imaging [WI], T2WI, and diffusion-weighted imaging [DWI], presence of the three rings appearance, and distinct low intensity areas at T2WI, presence of tree or dot-like components, degree of contrast enhancement), fallopian tube (dilatation, dilatation with haematoma, degree of contrast enhancement, enhanced components within the tube), and ascites. These findings were compared for non-CE and non-CE+CE-MRI data, and for expert and inexpert groups. RESULTS: The expert group identified implantation sites correctly in 58/63 (92%) cases for non-CE and non-CE+CE-MRI. In the inexpert group, the correct identification was improved from 54/63 (86%) using non-CE MRI to 58/63 (92%) using non-CE+CE-MRI, but was not significant ( p =0 . 29). In comparison between non-CE and non-CE+CE-MRI, dilation of the fallopian tubes was observed more frequently ( p =0 . 004) and the confidence level was elevated significantly in the non-CE+CE-MRI ( p <0 . 0001) in the inexpert group. Intergroup comparison revealed that confidence level was significantly higher in the expert group than in the inexpert group using non-CE MRI ( p <0 . 0001), although the difference was not significant at non-CE+CE MRI ( p =0 . 49). CONCLUSION: CE-MRI did not significantly improve correct identification of ectopic pregnancy implantation sites, although the addition of contrast enhancement did enable inexpert radiologists to diagnose confidently. Highlights: Contrast-enhanced MR images did not improve identification of implantation site. Reading experience did not influence the identification of implantation site. Inexpert readers might benefit from contrast-enhanced MR images.